Culturally Responsive Pedagogy: Exploring Parent Perspectives on American Education - Lakhwani, Monica (Journal of Interdisciplinary Studies in Education, 2023)
The United States has seen a growing number of Latinx, and half are of school-age. With the increasing numbers of Latinx students, it becomes essential to understand parent perspectives, feelings, and issues faced in order to be inclusive of and culturally responsive when working with diverse learners. This study utilized semi-structured interviews to identify Latinx parent perceptions on their child’s education in public educational institutions (K-postsecondary). This study results in Latinx parent perceptions on education, challenges, and messages for educators when working with Latinx child/children and their families. Themes include a difference in values, challenging factors, and cultural awareness knowledge. Understanding diverse views and possible challenges, may help educators integrate culturally responsive practices when working with Latinx students.